Gas separation using polymeric membranes: the recent development and its future - Hassan, Azman; Ismail, Ahmad Fauzi; Saidi, Hamdani (Faculty of Chemical and Natural Resources Engineering, 1991)
Membranes separation technology has been widely accepted as an alternative to the conventional separation techniques. Reverse osmosis, ultrafiltration and microfiltration are examples of the application of membrane separation technology which has been practiced in the chemical industry. Advances in these areas gradually led to development of membrane made from polymeric materials for gas separations. The polymeric membrane has found acceptance in a range of industrial, medical and laboratory applications. The paper will discuss the recent development, advantages, challenges, applications and future of polymeric membranes in gas separation applications.